Exploring connectivism in teaching english content subjects on high school students - Malave Tomala, Ximena Andrea (2024)
The present research aims to identify the Connectivism learning theory to explore ways of teaching English content subjects on high school students. The qualitative method was utilized through one-on-one interviews to gather the necessary information from the perceptions of six teachers on how connectivism works to teach various contents related to other subjects merging them with the English language. The findings of this research revealed that the practices of this theory are currently presented as a viable alternative for English teachers due to its innovative approach that tends to create a critical character inyoung students and foster collaboration among them through technology. Therefore, the mode in which educators utilize digital tools will depend on the skill they will focus on. This research will contribute essential information to educators who seek to broaden the basis of this theory to teach different contents in the target language from an avant-garde perspective.